1991
DOI: 10.1073/pnas.88.4.1217
|View full text |Cite
|
Sign up to set email alerts
|

Mouse hepatocytes migrate to liver parenchyma and function indefinitely after intrasplenic transplantation.

Abstract: One approach to gene therapy for hepatic diseass is to remove hepatocytes from an affected individual, genetically alter them in vitro, and reimplant them into a receptive locus. Although returning hepatocytes to the liver itself would be advantageous, the feasibility of this approach has never been evaluated due to the inability to distinguish donor from host hepatocytes. To unambiguously identify transplanted hepatocytes after transplantation, and to better quantitate their number and degree of liver functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
198
1
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(211 citation statements)
references
References 30 publications
9
198
1
3
Order By: Relevance
“…5,20 Previous estimates indicated that less than 20% of the transplanted hepatocytes survive long term in the liver. 8,21 Our data here show that transplanted cells are lost fairly early, as less than 30% of the hepatocytes were found in the liver at 24 hours after transplantation compared with at 2 hours after transplantation. Our morphometric analysis showed that not only were hepatocytes entrapped in portal areas lost, additional transplanted cells were lost from hepatic sinusoids as well.…”
Section: Discussionmentioning
confidence: 62%
“…5,20 Previous estimates indicated that less than 20% of the transplanted hepatocytes survive long term in the liver. 8,21 Our data here show that transplanted cells are lost fairly early, as less than 30% of the hepatocytes were found in the liver at 24 hours after transplantation compared with at 2 hours after transplantation. Our morphometric analysis showed that not only were hepatocytes entrapped in portal areas lost, additional transplanted cells were lost from hepatic sinusoids as well.…”
Section: Discussionmentioning
confidence: 62%
“…In this study partial hepatectomy or hepatic irradiation were not performed, and maybe the number of dead cells at the time of injection was not sufficient to create a permissive environment for hepatocyte engraftment. Nevertheless, these animals had some degree of lesion, as hepatocytes did remain in the spleen, and it has been suggested that this is required for the establishment of transplanted hepatocytes in rat spleens (20) .…”
Section: Discussionmentioning
confidence: 99%
“…70,72,73 These studies also showed that: (i) transplantation of normal hepatocytes as few as 1% of the patient liver mass could lead to metabolic benefits; 73 (ii) hepatocyte transplantation was safe in babies, therefore raising perspectives for ex vivo gene therapy in early stages of liver diseases; 70 (iii) repeated hepatocyte infusions (fresh and/or cryopreserved hepatocytes) allowed to obtain metabolic benefits; 70,72 and (iv) hepatocyte transplantations were insufficient to fully correct the metabolic liver diseases, therefore re-emphasizing the limitations of hepatocyte transplantation, in particular the inefficient repopulation of the recipient liver by donor cells. 1,74,75 Understanding the transplantation mechanisms, engraftment and repopulating ability of transplanted hepatocytes is therefore critical for defining suitable strategies to increase the transplanted hepatocyte mass.…”
Section: Hepatocyte Transplantation In Humansmentioning
confidence: 99%
“…77,79,80 Subsequently, translocated cells integrated into the liver parenchyma, regained their polarity with the formation of gap junctions and bile canaliculi between transplanted and host hepatocytes within about 1 week, without any significant proliferation in adult animals and were functional throughout the life of animals. 74,75,81 Overall, only 20-30% of transplanted hepatocytes integrated into the liver. For instance, transplantation of 2 Â 10 7 hepatocytes led to the repopulation of about 0.5% of the host liver by transplanted cells.…”
Section: Hepatocyte Transplantation Mechanismsmentioning
confidence: 99%